SEBARAN FRAKSI AL PADA PROFIL TANAH MASAM LAHAN KERING DI KABUPATEN LEBAK PROVINSI BANTEN - Putra Utama; Sri Ritawati; Dewi Firnia (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2019)
ABSTRACTThe toxicity of Al, Fe, and Mn is highly determined by the shape of the metalfractions. Therefore, the specific forms of Al, Fe, and Mn inside the soil are veryimportant to know because they are related to soil fertility. The purpose of this study was to determine the distribution of the Al fraction on the acid soil profile of dry land in Lebak Regency, Banten Province. This research was conducted from April to June 2019 in Maja District, Lebak Regency, Banten. The research was descriptive explorative with intentional sampling for special purposive sampling. The soil was tested with a main parameter using single extraction for Al Fractionation. The results showed that the Al fraction in amorphous form (Al-o) was more dominant than Al in dissolved form (Al-dd) in all horizon layers (0-120 cm). Moreover, the Al fraction in organic amorphous form (Al-p) was also more dominant than Al in the inorganic amorphous form (Al-po) at horizon layer of 0-15 cm, while at horizon laeyer of 15-120 cm the Al-po form was higher than Al-p. Al fraction in the form of organic amorphous had higher bond compared with Al form of organic amorphous in the soil layer of 0-120 cm.